UJARAN KEBENCIAN PADA KOMENTAR TIKTOK @OFFICIALRCTI TERHADAP MARISA PESERTA X FACTOR INDONESIA - Nur Azizah; Dhella Patrichia Chandra; Ian Wahyuni (Universitas PGRI Palembang, 2024)
This research aims to analyze and find out hate speech that leads to insulting one of the contestants at the X Factor Indonesia 2024 event by focusing on the comments column on the TikTok account @officialrcti. This type of research is descriptive qualitative research by connecting the theories of Pragmatics and Forensic Linguistics. The data used in this research is in the form of netizen comments on the tiktok account @officialRcti. This research will identify hate speech uttered by netizens in the comments column regarding Marisa's appearance as a contestant on X Factor Indonesia 2024 by understanding the context of pragmatic theory, followed by analysis based on the type of marginalization of hate speech and linking it to the theory of Forensic Linguistics contained in article 156 paragraph 1 of the Criminal Code and UU article 28 paragraph 2 of the ITE Law. The results of this research are to provide knowledge about hate speech in language or insight into understanding Forensic Linguistics.